Exploring stress tolerance indices to identify terminal heat tolerance in spring wheat in Nepal - Puri, Ramesh Raj; Gautam, Nutan Raj; Joshi, Arun Kumar (Journal of Cereal Research, 2025)
Terminal heat stress during anthesis and grain filling period accelerates maturity and significantly reduces grain size and weight. A study was performed to explore stress tolerance indices that can judge terminal heat tolerance in spring wheat in Nepal. Ten diverse lines were planted under normal (non-stress) and late (heat stress) sown condition at two locations (Parwanipur and Hardinath) in Nepal. The trial was set up in Alpha Lattice design with two replications in two consecutive crop cycles 2011-12 and 2012-13. Yield traits were recorded and stress susceptibility and tolerant indices were estimated. Correlation analysis showed that yield under stress environment had positive (r=0.80) and significant (p